Closing the Communal Gap: The Importance of Communal Affordances in Science Career Motivation - Brown, Elizabeth R. (J Appl Soc Psychol, 2015)
To remain competitive in the global economy, the United States (and other countries) is trying to broaden participation in science, technology, engineering, and mathematics (STEM) by graduating an additional 1 million people in STEM fields by 2018. Although communion (working with, helping, and caring for others) is a basic human need, STEM careers are often (mis)perceived as being uncommunal. Across three naturalistic studies we found greater support for the communal affordance hypothesis, that perceiving STEM careers as affording greater communion is associated with greater STEM career interest, than two alternative hypotheses derived from goal congruity theory. Importantly, these findings held regardless of major (Study 1), college enrollment (Study 2), and gender (Studies 1–3). For undergraduate research assistants, mid-semester beliefs that STEM affords communion predicted end of the semester STEM motivation (Study 3). Our data highlight the importance of educational and workplace motivational interventions targeting communal affordances beliefs about STEM.